Myelodysplastic Neoplasms: The Impact of Clonality on Inflammatory-Degenerative Diseases of the Elderly - Nicolas Bonadies (healthbook TIMES. Oncology Hematology)
The diagnostic approach to patients with cytopenia has become highly challenging due to the heterogenic presentation of clonal hematopoietic stem cell disorders and accompanying degenerative disorders in the generally elderly population. A holistic approach with extensive clinical experience is required to recognize the potential interactions between the clonal condition and inflammatory-degenerative comorbidities in the elderly. This narrative review highlights the diagnostic challenges in the classification and risk stratification of patients with clonal hematopoiesis and myelodysplastic neoplasms, dysregulation of immune hemostasis and its impact on degenerative-inflammatory comorbidities of the elderly from the perspective of an experienced clinician.